Indicadores de patentes para o monitoramento tecnológico em aços para dutos utilizados em transporte de hidrocarbonetos - Oliveira, Bráulio Salumão de (2016)
Most part of the hydrocarbons reserves used in the global energy matrix are far from their main consumer markets. One of the most technically and economically viable means for such transport is carrying it out through pipelines, mostly built in steel. Technical challenges such as low temperatures and acid environments demands innovative products and processes that, consequently, require research and development of new materials and processes. This study aimed to analyze the technological development of steel for hydrocarbons pipelines through the patent indicators from documents indexed in the Derwent Innovations Index base between the years 1971 and 2014. The developed indicators includes temporal evolution, life cycle of technology, identification of the alloying elements, technologies for products processing and properties required, and also comparison among major developers and their interest markets. The number of patent documents on the subject increased significantly during the study period. Some countries stand out due to the number of patent applications with different behaviors about their inventions protection along other territories. The main holders are Japanese companies while China was the country that had the highest growth trend of deposits in steels for pipelines. The most prominent alloys were those containing manganese, chromium, molybdenum and titanium additions, and these are intended to assist in the technological challenges, like the improvement of mechanical properties and resistance to sour environments, while in terms of production processes, the most cited were rolling followed by heat treatments and thermomechanical processes. An analysis from alloys containing manganese at levels above 1.5 wt. % evidences that patent documents in this sector anticipates standards, at least regarding the amount of alloying elements present in the steels.